Development of freeze-dried jackfruit (Cartocarpus heterophylla) - Lopez, Micaela de Ocampo; Azanza, Ma. Patricia V. (2000.)
ABSTRACT This study primarily aimed to develop freeze-dried jackfruit with high consumer acceptable quality characteristics. This study was divided into 3 phases: determination of variety of jackfruit for freeze-drying, stanardization of the jackfruit freeze-drying process, and product characterization. The first phase of this study involved the selection of the appropriate variety (Sinaba or Tinumbaga) of jackfruit to be used for the study. The ripe Sinaba and Tinumbag varieties were freeze-dried under condenser temperature of -45°C and vacuum pressure of -48° mm Hg. Color, pH, moisture content, water activity, firmness and yield were used to evaluate the samples. The Tinumbaga jackfruit was selected to be used further in the study based on better yellow color, appropriate moisture content and a firmer flesh, of the fresh and freeze-dried samples. Phase II aimed to determine the level of maturity of the Tinumbaga jackfruit appropriate for freeze-drying. Objective test used in Phase I was again used to compare the rare ripe and ripe maturities, a pseudo-sensory evaluation was also performed to choose the right maturity level. Other quality parameters of the rehydrated sample including rehydration ratio, percent water uptake and percent chalky area were computed. the ripe sample of Tinumbaga jackfruit was chosen as the appropriate level of maturity for freeze-drying because of the better yellow color, appropriate moisture content and more acceptable firmness. Also, the ripe freeze-dried sample had better rehydration ratio and percent water uptake and chalky area was absent. Reults showed that the freezr-dried ripe sample had an overall acceptability rating of like moderately, as compared to the overall acceptability rating of the rare ripe sample, being neither like nor dislike. The rehydrated ripe sample had an overall acceptability rating of like slightly while the rehydrated rare ripe sample obtained a mean score corresponding to an acceptability rating of dislike slightly.P
Thesis (BSFT)--University of the Philippines Diliman
Keywords: Fruit -- Preservation